Letting Rivals Come Close or Warding Them Off? The Effects of Substitution Threat on Imitation Deterrence - Polidoro, Francisco; Toh, Puay Khoon (Academy of Management Journal, 2011)
A resource-based theory postulate is that firms must defend their resources against imitation to sustain competitive advantage. However, by deterring imitation, firms may induce rivals to create substitutes. This study shows that, contrary to received wisdom, firms are not uniformly inclined to deter resource imitation. Rather, this inclination decreases in response to substitution threat. By examining how firms manage the trade-off between inimitability and nonsubstitutability, this study suggests that the scenario wherein firms have omnipotent resources that are both inimitable and nonsubstitutable may be unrealistic and that managing the tension between these two attributes is key to sustainable competitive advantage.